Uma caracterização sobre apropriação do método intuitivo de Calkins para saberes aritméticos do ensino primário em revistas pedagógicas brasileiras (1891-1931) - Nascimento, Josefa Lourença Souza do (2018)
In this text are the result of a research that aimed to characterize the appropriations intuitive method of Calkins (1886/1950) for teaching arithmetic, knowledge in pedagogical journals produced in different Brazilian States in the period of 1891 to 1931. Understanding of Valens (2015) were used to treat about elementary mathematical knowledge, Ragazzini (2001) about historical sources, Chartier (2003) for ownership and Calkins (1886/1950) to the principles of intuitive method. As sources were used copies of Brazilian journals available on the digital repository at UFSC. To examine such sources were taken two ways, the first was examined articles bringing explicit references to Calkins for teaching arithmetic of knowledge, and the second, examination of articles addressed implicit manner the principles of method intuitive of the author. To walk these paths, it was possible to characterize the appropriations from knowing how arithmetic: number, fraction operations and measure, which had the objective to stimulate the senses of the child, mainly from the view. The authors adopted principles of intuitive method of Calkins (1886/1950) leaving mainly questions, urging students to view the objects, such as lathes, toothpicks, chopsticks, paper circles, Parker and frames, for the construction of ideas of knowledge. The Association and the comparison were also identified in the treatment of education, since the student was also conducted to associate knowledge retained in memory, the new ideas, as well as, to relate quantity to your representative and signs compare sizes. The examination of articles allowed to characterize the appropriations intuitive method of Calkins (1886/1950) for teaching arithmetic of knowledge in the following ways: first, through the observation of objects, recommendation identified in seventeen articles. The second, through the imagination, in that the principles should be encouraged to join the know the practical examples. The third form of ownership, would be accomplished through recreational activities.